THE VALIDITY OF STUDENT WORKSHEET PROJECT BASED LEARNING AS AN EFFORT TO APPLY STUDENTS CONSEPTUAL FOR 10th GRADE IN SENIOR HIGH SCHOOL - Desy Tegar Puspitaningtyas; Ulfi Faizah (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
AbstractThe student got the material concept of animalia in the class is expected to be able to applied the concept because of time constraints so that it can be done through project-based learning that are supported by a students worksheet in helped to appplied the concept of animalia. The consept of animalia is to classify animals into phylum. The purpose of this research was to describe the validity of a project-based learning worksheet of Animalia topics based on expert validity. This research used development model 4-D (define, design, develop, and disseminate), but the disseminate phase was not conducted. The result of this research based on authorities with eligibility criteria presentation of 95.38%; the feasibility of the content of 98.66%, and the feasibility of language of 98.63% so got the average of 97.34% that were categorized as valid. So, can be concluded that project-based learning worksheet was worthy to be tested is limited to students.Keywords: Project-based Learning, Worksheet, Animalia Topics